Stock Market Prices and Performance of Textile Industry of Pakistan in Last Five Years – An Evidence of EMH - Aamir, Muhammad; Khan, Kanwal Iqbal; Rehan, Muhammad Farooq (Richtmann Publishing, 2012)
This paper explains the performance of the textile sector and its impact on the market prices for the last five years. Textilesector is an important sector for the economy of Pakistan due to its employment potential, availability of raw material and foreignexchange earnings but this sector is not contributing its required role in the economy since the last five years. Why textile industry haslost its share in exports and fails to maintain its position in the economy. Reasons are discussed and explained by building the statisticalrelationship between the performance of the companies and their market prices. Although there are many internal and external factorsfor measuring the performance of the company, but in this research article only EPS (Earning per Share) and Book Value of shares aretaken as a performance measurement tools. The efficient market hypothesis is used as an evidence to explain the relationship betweenthe stock market prices and performance of the textile industry. The sample of twenty companies are taken from textile industry and byusing the SPSS software the relationship between the performance of the companies and their market prices are explained in themeaningful way. These results are helpful in explaining, how performance of the textile industry affects their market prices of shares inthe stock market.